Cognition and hospitalizations are linked with salivary and faecal microbiota in cirrhosis cohorts from the USA and Mexico. (1st April 2020) - Bajaj, Jasmohan S.; Torre, Aldo; Rojas, Mayra L.; Fagan, Andrew; Nandez, Ivvone E.; Gavis, Edith A.; De Leon Osorio, Omar; White, Melanie B.; Fuchs, Michael; Sikaroodi, Masoumeh; Gillevet, Patrick M.
Abstract: Background & Aims: Gut microbiota are affected by diet and ethnicity, which impacts cognition and hospitalizations in cirrhosis. Aim: Study interactions of diet with microbiota and impact on hospitalizations and cognition in American and Mexican cohorts. Methods: Controls and age‐balanced patients with compensated/decompensated cirrhosis were included and followed for 90‐day hospitalizations. A subset underwent minimal hepatic encephalopathy (MHE) testing. Parameters such as dietary, salivary and faecal microbiota (diversity, taxa analysis, cirrhosis dysbiosis ratio CDR:high = good) between/within countries were analysed. Regression analyses for hospitalizations and MHE were performed. Results: In all, 275 age‐balanced subjects (133 US [40 Control, 50 Compensated, 43 Decompensated] and 142 Mexican [41 Control, 49 Compensated, 52 Decompensated]) were enrolled. MELD/cirrhosis severity was comparable. Diet showed lower protein and animal fat intake in all decompensated patients, but this was worse in Mexico. Diversity was lower in stool and saliva in decompensated patients, and worse in Mexican cohorts. Prevotellaceae were lower in decompensated cirrhosis, particularly those with lower animal fat/protein consumption across countries. Hospitalizations were higher in Mexico vs the USA (26% vs 14%, P = .04). On regression, Prevotellaceae, Ruminococcaceae and Lachnospiraceae lowered hospitalization risk independent of MELD and ascites. MHE testing was performed in 120 (60/country and 20/subgroup) subjects and MHE rate was similar. MELD and decompensation increased while CDR and Prevotellaceae decreased the risk of MHE. Conclusions: Changes in diet and microbiota, especially related to animal fat and protein intake and Prevotellaceae, are associated with MHE and hospitalizations in Mexican patients with cirrhosis compared to an American cohort. Nutritional counselling to increase protein intake in cirrhosis could help prevent these hospitalizations.